2007
DOI: 10.1007/s12020-007-9014-1
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone upregulation of tissue type plasminogen activator expression in Sertoli cells

Abstract: Our previous studies have demonstrated that tissue type plasminogen activator (tPA) might be involved in matrix degradation of blood-testis barrier in rat. In this study, we have further investigated the effect of testosterone (T) on tPA production in rat Sertoli cells. Our results showed that Sertoli cells isolated from rat testes at various ages in vitro secreted tPA in an age-dependent manner. The tPA activity was detected on day 20 after birth, and reached maximum on day 60. The Sertoli cells isolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 50 publications
0
14
1
Order By: Relevance
“…In these altered genes, the genes from signaling pathways for cell adhesion, focal adhesions, tight junctions and gap junctions were enriched ( Supplemental Fig. 4 ), including junction genes (Cx43, JAMA, claudin11, claudin1, claudin5) and BTB regulators (matrix metalloproteinase 2 (MMP2), MMP17, intercellular adhesion molecule 1 (ICAM1) and tissue-type plasminogen activator (TPA)) 40 41 42 ( Fig. 3C , left table).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these altered genes, the genes from signaling pathways for cell adhesion, focal adhesions, tight junctions and gap junctions were enriched ( Supplemental Fig. 4 ), including junction genes (Cx43, JAMA, claudin11, claudin1, claudin5) and BTB regulators (matrix metalloproteinase 2 (MMP2), MMP17, intercellular adhesion molecule 1 (ICAM1) and tissue-type plasminogen activator (TPA)) 40 41 42 ( Fig. 3C , left table).…”
Section: Resultsmentioning
confidence: 99%
“…3B and unpublished data). Furthermore, Shp2 deletion altered the expression of several junction genes, such as claudin 1, claudin 11 and TPA 40 42 . These results suggested that Shp2 mediates BTB formation by regulating the expression and localization of junctional complex proteins.…”
Section: Disscussionmentioning
confidence: 99%
“…In adulthood, FSH drives Sertoli cells to produce regulatory molecules and nutrients required for spermatogenesis [18]. In particular, FSH activates the transcription of genes involved in metabolic homeostasis and supports germ cell functions [16], with the synthesis of retinoic acid, lactate, type 2 plasminogen activator, as well as fatty acid metabolism and mitochondrial biogenesis [19,20]. FSH circulating levels correlate directly with Sertoli cell number and testicular volume in adults [21].…”
Section: Physiological Control Of Spermatogenesismentioning
confidence: 99%
“…3). Sertoli and granulosa cells express enzymes that cleave proAMH, with the levels of the enzymes and/or their regulators varying during testicular (Nachtigal & Ingraham 1996, Guo et al 2007, Le Magueresse-Battistoni 2007, Uhrin et al 2007) and ovarian (Bae et al 2008) development, the seminiferous cycle (Guo et al 2007, Le Magueresse-Battistoni 2007, Uhrin et al 2007, the ovarian cycle (Bae et al 2008, Wang et al 2014, the stage of ovarian follicular development (Ohnishi et al 2005, Bae et al 2008, Antenos et al 2011) and during pregnancy (Kwok et al 2013). However, the AMH in ovine follicular fluid is predominantly proAMH with little AMH N,C (Campbell et al 2012), suggesting that AMH can be synthesised and released with little or no prior cleavage.…”
Section: Gonadal Cleavage Of Proamhmentioning
confidence: 99%